2022
DOI: 10.4322/rae.v16e202202
|View full text |Cite
|
Sign up to set email alerts
|

Análise de Confiabilidade de Software na Análise Biomecânica: Revisão de Literatura

Abstract: Uma análise biomecânica no intuito de identificar riscos e alterações observa a sobrecarga exposta ao corpo, assim como posturas que podem levar a uma lesão. A utilização de ferramentas auxilia na identificação de possíveis riscos. O uso de software confiável e projetado se torna eficaz na avaliação. Este estudo teve como objetivo investigar a confiabilidade do uso de software na análise biomecânica. Foi realizada uma revisão de literatura de artigos com base de dados dos últimos dez anos, nas plataformas de d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…To carry out the evaluation of the hallux (mis)alignment, computerized photogrammetry was used. Despite the growing number of studies that use computerized photogrammetry [23][24][25][26][27], there are no reference values on its use in the evaluation of Hallux Valgus; likewise, few studies were found that verified the reliability of these measurements. One this study found [28] refers to the evaluation of Hallux Valgus through the use of self-photography.…”
Section: Hallux (Mis)alignment Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…To carry out the evaluation of the hallux (mis)alignment, computerized photogrammetry was used. Despite the growing number of studies that use computerized photogrammetry [23][24][25][26][27], there are no reference values on its use in the evaluation of Hallux Valgus; likewise, few studies were found that verified the reliability of these measurements. One this study found [28] refers to the evaluation of Hallux Valgus through the use of self-photography.…”
Section: Hallux (Mis)alignment Evaluationmentioning
confidence: 99%
“…To standardize the recording of images, a Webcam Logitech ®® 920 was used, fixed on a tripod 45 cm away from the anterior region of the foot (Figure 3), with a leveling control in relation to the ground to allow the perpendicular capture of images analyzed in a transverse plane, reducing the margins of error in the reproduction of evaluations. Kinovea ® software was used to analyze the collected images (Figure 4), which is recognized for having good reliability with results over 90% in the biomechanical analysis [26].…”
Section: Hallux (Mis)alignment Evaluationmentioning
confidence: 99%
See 1 more Smart Citation